1-April Problem of the Week. Issue#21

Simplify the expression:

(x – a)·(x – b)·(x – c)·… ·(x – online casino slots z) =


(A) x·(a b c … z)

(B) x^26 x^25·a x^24·a·b … x·a·b·c·d·…·z

(C) x·a·b·c·…·z

(D) x^26 x^25·a x^24·(a b) … x·(a b c d … z)

(E) 0

9 thoughts on “1-April Problem of the Week. Issue#21

Leave a Reply to Roman Drachev Cancel reply

Your email address will not be published. Required fields are marked *


You may use these HTML tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <strike> <strong>